Diallel analysis of seven quantitative traits in deshi jute (Corchorus capsularis L.) (Bangladesh Journal of Botany, 2011)
Genetic constitution of yield and its associated traits of Corchorus capsularis L. was investigated using a 10 × 10 full diallel cross experiment. Additive gene action system with partial dominance was predominat for plant height, technical height, base diameter and number of nodes in F1. Non-allellic interaction was involved in the inheritance of bark weight and stick weight in F2. The Vr - Wr graph for bark weight and fibre weight of F1 and F2 showed an additive genetic system with dominance effect. The parents Acc. 4087 and var. A-38 possessed maximum number of dominant alleles for most of the characters. Acc.1833 possessed an excess of recessive genes for all the characters. Key words: Diallel analysis; Inheritance; Dominance effect; Corchorus capsularisDOI: 10.3329/bjb.v39i2.7299 Bangladesh J. Bot. 39(2): 137-141, 2010 (December)